Contact Lenses in Aphakia : Aphakic Surgery and its Implications for Contact Lens Fitting - Ruben, C.M. (Canadian Journal of Optometry, 2021)
This paper discusses complications deriving from cataract extraction which are relevant to the fitting of contact lenses.